A Review of Operations Management in Treatment Plant Materials - Hisham, Mat Desa @ Husain (2016)
A review of Operations Management in Treatment Plant materials to control the water systems that is very important to the overall operation of the powerhouse and to the success of the chemical treatment program. Proper control results in a clean boiler, and a clean boiler improves energy efficiency and boiler reliability. Good control saves money, conserves energy. The steam produced in the boilers must be of acceptable quality, as dictated by the operations for which it is intended. The first support system is the pre-treatment system. As the name implies, water is first treated before it reaches the boiler. The general purposre-treatment is to remove both suspended and soluble solids that, if not removed, could lead to boiler deposits and poor steam quality. These problems, in turn, could lead to inefficient boiler operation and ultimately to boiler and/or plant shutdown. The second boiler support system is the feed-water system. Feed-water system is basically the final stream of the water that enters the boiler. It is composed of water from the pre-treatment system plus any water from the condensate system can result. The third support is chemical treatment. Good monitoring of chemical reserve and right practice can prevent the corrosion and scaling tendency. It is imperative that each support system be at its best if the entire boiler system is to operate efficiently. Otherwise, maintenance costs and process inefficiency, and ultimately a plant or process shutdown could occur.